Development of Art Education Management Model in the Digital Era of Private Universities in Henan Province - Xu, Xin; Siththada, Thada (วารสารการวิจัยการบริหารการพัฒนา, 2025)
This article aims to: 1.To study the levels of art education management in the digital era of private universities in Henan Province. 2. To study the exploratory factors analysis of art education management in the digital era of private universities in Henan Province. 3.To propose the guideline for development of art education management model in the digital era of private universities in Henan Province. This study used the EFA methodology.The research design is mixed methods research. The study is framed by the concept of takes into account the policies and current situation of education development in private universities in Henan Province, and explores the development of art education models in the digital age in private universities in Henan Province. The research area explores factors for developing of art education management model in the digital era of private universities in Henan Province. for developing of art education management model in the digital era of private universities in Henan Province. Include of Learners’ engagement，Industry Cooperation，Course relevance，Teacher Expertise Technical infrastructure. It examines the current state and existing cha challenges of art education management in the digital in these universities, aiming to propose countermeasures and suggestions for improvement. The target group key consists of in this research was administrators and teachers at private universities in Henan Province. This study used the EFA methodology. The survey targets art education administrators and teachers in the digital era of private universities in Henan Province, the sample group used 36 private universities in Henan Province. The researcher has assigned 14 respondents consist of 4 school administrators and 10 teachers for each private university. Therefore, there are 504 respondents of school administrators (144 respondents) and teachers (360 respondents), And the content analysis by 9 key informants. The research tools consist of five types: 1.By systematically retrieving, screening, and analyzing published academic literature, reports, policy documents, etc., we can obtain the theoretical framework, research status, methodological paradigms, and controversial focuses in the research field. 2.Through standardized question design, questionnaires are distributed to the target group to collect quantitative data for analyzing the relationships (such as correlation and difference) between variables. Conduct Cronbach’s α reliability analysis (α>0.7 indicates reliability) and factor analysis (KMO>0.6) through pre-survey to ensure the quality of the questionnaire. 3.Quantitative data collected from the questionnaire was analyzed using SPSS software. Descriptive statistics were used to analyze the demographic characteristics of the participants as well as the mean and standard deviation of each variable. An exploratory factor analysis was conducted to determine the factors underlying the influence of art education management in digital era on private education management and to test the reliability and validity of each factor. 4. The five-expert interviewing. Through semi-structured or unstructured dialogues, we conduct in-depth exchanges with interviewees to obtain qualitative data such as subjective experiences, behavioral motivations, and situational details. 5.The nine-expert interviewing. Through semi-structured or unstructured dialogues, we conduct in-depth exchanges. Data were analyzed using: 1. Qualitative exploration stage theoretical construction and preliminary screening of factors 2. Systematic Literature Review: Based on databases such as Web of Science Core Collection and CNKI Academic Journal Database, cross language searches were conducted using keyword combinations such as "Digital Transformation of Art Management Private Universities". 3. Delphi expert interview: Using a purposive sampling strategy, five composite experts with associate senior titles or more or more than ten years of management experience were selected (including two scholars in the field of art management, two managers from private universities, and one industry association leader). A theoretical framework for the influencing factors of digital art management mode has been preliminarily constructed. ​4. Quantitative verification stage: hypothesis testing and model construction: The development of measurement tools is adapted from mature scales at home and abroad for confirmatory factor analysis to ensure the structural validity of the scales. Use SPSS for descriptive statistics and construct a standardized regression equation model. 5.Qualitative deepening stage: expert consensus verification: A second round of expert interviews was conducted, and 9 new industry experts (including art institution leaders, education information technology experts, and university teaching supervisors) were added through snowball sampling. Using a combination of focus group interviews and in-depth case analysis, multidimensional validation is conducted around the core influencing factors, action paths, and model interpretability identified through quantitative research. 6.Research on Reliability and Validity Assurance System 7.Conclusion validity: Expert cross validation and multi case comparative analysis are adopted to ensure the theoretical saturation and practical universality of the research conclusions Research findings: 1.The findings related to the first objective indicate the current art education models in Henan Province’s private universities are reasonably aligned with digital demands. 2.that the findings related to the second objective reveal that five key factors influencing art education models were identified: Course relevance, teacher Expertise, Technical Infrastructure, Industry Cooperation, and Learners engagement. 3.that the findings related to the third objective reveal that propose the guideline for developing of art education management model in the digital era of private universities in Henan Province. Contribution: The findings of this study provide new perspectives and insights into higher education theories in the digital environment. By focusing on private universities in Henan Province, this study will expand on existing theories of private higher education management and provide a theoretical framework for specific regions and specific types of institutions. Through theories of multiple factors such as learner engagement, teacher career, and data platform, the study deeply explores how technology in the digital age affects and changes art education, providing new insights into the integration theory of educational technology.